The Development Of Social Studies Learning And Assessment Materials Based On Local Potential For Secondary School - Dwi Atmono; Muhammad Rahmattullah; Sri Setiti (STAI Miftahul Ula Nganjuk, 2019)
This research aimed to analyze student needs in social studies classroom in purpose to design learning model using local potential in Banjarmasin area. This research used qualitative approach. Data collected through literature analysis, observation, and interviews through focus group discussion and focused on 7th grade materials. Data analyzed with qualitative method. The result showed that those are seven basic competences on 7th grade that can be developed for social studies learning with the using of local potential. Learning process can be applied through direct and indirect methods, interactive learning, independent learning, field observation, and discussion. It required supplement books based on local potential, the increasing of MGMP’s empowerment for social studies teachers, teachers’ training on learning planning, process, and evaluation based on local potential, and the developing of learning media through film documentary with local potential contents. In term of curriculum changing, to increase teachers’ competence in assessment it required training about authentic assessment, classroom assessment, character based assessment, and competence based assessment. It is necessary to create local potential roadmap as guidance for social studies learning material in Banjarmasin as the implementation of local excellence and character education for social studies learning.